2020
DOI: 10.1021/acs.jpcc.0c03589
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evolution in Methylammonium Tin Halide Perovskites with Variable Temperature Solid-State 119Sn NMR Spectroscopy

Abstract: Hybrid organic−inorganic metal-halide perovskite materials are an emerging class of materials that could profoundly change the optoelectronic and solar absorber research fields and have far-reaching applications. Unfortunately, the leading solarabsorbing candidates are lead-containing materials and suffer from chemical instability, eventually decomposing, resulting in detrimental long-term environmental concerns. A series of nontoxic group 14 Sn(II)-based hybrid organic−inorganic metal-halide perovskites is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 92 publications
6
33
0
Order By: Relevance
“…However, solid-state nuclear magnetic resonance (NMR) spectroscopy is an invaluable method to investigate local structure (e.g., halide distribution, domain structure) and dynamics in perovskites. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In particular, 133 Cs (I ¼ 7/2, 100% abundance) and 119 Sn (I ¼ 1/2, 8.59% abundance) are ideal NMR-sensitive nuclei, useful for probing the local structure of the A and B sites in perovskites ABX 3 , 30,37,[39][40][41][42][43][44][45] as well as of sites in other types of compounds. [46][47][48][49] Here we target the preparation of CsSn(Cl 1Àx Br x ) 3 to ascertain if a complete solid solution with the cubic perovskite structure can be attained for the entire range.…”
Section: Introductionmentioning
confidence: 99%
“…However, solid-state nuclear magnetic resonance (NMR) spectroscopy is an invaluable method to investigate local structure (e.g., halide distribution, domain structure) and dynamics in perovskites. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In particular, 133 Cs (I ¼ 7/2, 100% abundance) and 119 Sn (I ¼ 1/2, 8.59% abundance) are ideal NMR-sensitive nuclei, useful for probing the local structure of the A and B sites in perovskites ABX 3 , 30,37,[39][40][41][42][43][44][45] as well as of sites in other types of compounds. [46][47][48][49] Here we target the preparation of CsSn(Cl 1Àx Br x ) 3 to ascertain if a complete solid solution with the cubic perovskite structure can be attained for the entire range.…”
Section: Introductionmentioning
confidence: 99%
“…36,42,47,49-52 119 Sn (I = 1/2, 8.6% abundance), the most receptive nucleus among three NMR-active tin isotopes ( 115 Sn, 117 Sn, 119 Sn) (Table S1), 48 has been used to resolve the local B-site structural environments and halogen dynamics in ABX3 perovskites and other tin-containing compounds. 16,17,[53][54][55][56][57][58][59] Furthermore, the 119 Sn NMR spectra displays an extensive range to diamagnetic Sn-containing compounds which has been recently extended to span nearly 6,000 ppm. 16,[60][61][62] This study shows an impressive ability to tailor the optical bandgap over a 3 eV range using a high energy mechanochemical synthetic design of vacancy ordered double perovskite Cs2SnClxBr6−x and Cs2SnBrxI6−x mixed-halide materials.…”
Section: Introductionmentioning
confidence: 99%
“…The trend of increased Sn shielding (to lower frequency) with increased halogen atomic number observed here, a normal halogen dependence (NHD), is opposite to previous studies on Sn(II)-based perovskites (ASnX3), where an inverse halogen dependence (IHD) was observed with a smaller chemical shift range (< 1300 ppm). 16,56,66 The unprecedented change in 119 Sn chemical shift was further studied using theoretical calculations, which revealed that the diamagnetic and paramagnetic shielding terms are nearly unchanged. Hence, the changes in chemical shift originate from considerable spin-orbit effects whereby this term changes ca.…”
Section: Introductionmentioning
confidence: 99%
“…36,42,47,49-52 119 Sn (I = 1/2, 8.6% abundance), the most receptive nucleus among three NMR-active tin isotopes ( 115 Sn, 117 Sn, 119 Sn) (Table S1), 48 has been used to resolve the local B-site structural environments and halogen dynamics in ABX3 perovskites and other tin-containing compounds. 16,17,[53][54][55][56][57][58][59] Furthermore, the 119 Sn NMR spectra displays an extensive range to diamagnetic Sn-containing compounds which has been recently extended to span nearly 6,000 ppm. 16,[60][61][62] This study shows an impressive ability to tailor the optical bandgap over a 3 eV range using a high energy mechanochemical synthetic design of vacancy ordered double perovskite Cs2SnClxBr6−x and Cs2SnBrxI6−x mixed-halide materials.…”
Section: Introductionmentioning
confidence: 99%